Determinant Fraudulent Financial Reporting Pada Perusahaan Sektor Perbankan di Indonesia Perspektif Fraud Hexagon Theory - Fadli Nuryasin; Eko Pujiyono (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the determinants of fraudulent financial reporting in banking companies listed on the Indonesia Stock Exchange using the Fraud Hexagon Theory approach. The variables tested include pressure, opportunity, rationalization, capability, arrogance, and collusion. This research uses a quantitative method with a panel data regression approach, based on secondary data from annual reports and financial statements for the 2023–2024 period. The results indicate that fraudulent financial reporting is influenced by internal and external factors reflected in the six elements of the Fraud Hexagon. This study highlights that pressure and opportunity tend to have a dominant role in encouraging fraud, while other variables show varying influences. The findings provide implications for regulators and investors in strengthening supervision and improving decision-making accuracy.